2023
DOI: 10.2174/1871530323666221208111823
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy-Associated Hypophysitis under Anti-PD1: Two Case Reports

Abstract: Background: Immunotherapy-associated hypophysitis is an uncommon adverse event. However, if not handled properly, it could lead to fatal sequelae. Case description: Case 1. A 66-year-old man presented to our hospital with hyponatremia. He had low plasma levels of adrenocorticotropin and cortisol. The patient had a history of non-small cell lung cancer and had undergone 16 cycles of immunotherapy with sintilimab, a monoclonal antibody against programmed cell death protein 1 (PD1). He was diagnosed with adrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In fact, there are little publication about immune factors and its relationship with the development of hyponatremia caused by impairment of pituitary. Although some case reports reported hyponatremia in immunotherapy-associated hypophysitis patients [ 25 – 27 ], it is difficult to find a corresponding role of immune factors in hypophysitis and pituitary adenoma. In the current research, the observed trend in WBC count and monocyte percentage may suggest a potentially less effective immune response to surgical injury, which in turn could have an impact on ADH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are little publication about immune factors and its relationship with the development of hyponatremia caused by impairment of pituitary. Although some case reports reported hyponatremia in immunotherapy-associated hypophysitis patients [ 25 – 27 ], it is difficult to find a corresponding role of immune factors in hypophysitis and pituitary adenoma. In the current research, the observed trend in WBC count and monocyte percentage may suggest a potentially less effective immune response to surgical injury, which in turn could have an impact on ADH secretion.…”
Section: Discussionmentioning
confidence: 99%